The Role of Escherichia coli Shiga Toxins in STEC Colonization of Cattle - Christian Menge (Toxins, 2020)
Many cattle are persistently colonized with Shiga toxin-producing Escherichia coli (STEC) and represent a major source of human infections with human-pathogenic STEC strains (syn. enterohemorrhagic E. coli (EHEC)). Intervention strategies most effectively protecting humans best aim at the limitation of bovine STEC shedding. Mechanisms enabling STEC to persist in cattle are only partialy understood. Cattle were long believed to resist the detrimental effects of Shiga toxins (Stxs), potent cytotoxins acting as principal virulence factors in the pathogenesis of human EHEC-associated diseases. However, work by different groups, summarized in this review, has provided substantial evidence that different types of target cells for Stxs exist in cattle. Peripheral and intestinal lymphocytes express the Stx receptor globotriaosylceramide (Gb3syn. CD77) in vitro and in vivo in an activation-dependent fashion with Stx-binding isoforms expressed predominantly at early stages of the activation process. Subpopulations of colonic epithelial cells and macrophage-like cells, residing in the bovine mucosa in proximity to STEC colonies, are also targeted by Stxs. STEC-inoculated calves are depressed in mounting appropriate cellular immune responses which can be overcome by vaccination of the animals against Stxs early in life before encountering STEC. Considering Stx target cells and the resulting effects of Stxs in cattle, which significantly differ from effects implicated in human disease, may open promising opportunities to improve existing yet insufficient measures to limit STEC carriage and shedding by the principal reservoir host.